Analysis of sounding data from Porto Santo island during ASTEX - Schubert, Wayne H., author; Cox, Stephen K., author; McKee, Thomas B., author; Randall, David A., author; Ciesielski, Paul E., author; Kleist, John D., author; Stevens, Eric L., author (Colorado State University. Libraries, 1992)
We present an analysis of the ASTEX radiosonde data obtained on Porto Santo Island during 1-28 June 1992. The data consists of 203 soundings and is available in two forms-Level I and Level II. The Level I data is the raw data produced by the real time software of the AIR radiosonde system. This data is at irregular pressure and height levels. Level II data consists of processed thermodynamic and wind data at a uniform vertical resolution of 10m, which essentially retains the highest possible vertical resolution in the original raw data. Plots of temperature and dew point temperature are presented for each of the 203 soundings taken during ASTEX. Plots of the 28 day means and of the diurnal variations are also presented. Accessibility of this data via anonymous ftp is also discussed.
November 7, 1992.
Keywords: Meteorology -- Madeira -- Porto Santo; Sounding and soundings